A high-strength and low-density ceramsite fired at low temperature using foundry ash and a preparation method thereof

By using raw materials such as casting ash and AC foaming agents, combined with low-temperature firing and granulation technology, the contradiction between density and strength of ceramic particles in building materials is solved, and the effect of low density and high strength of ceramic particles is achieved.

CN117800757BActive Publication Date: 2025-04-18LIUZHOU LIUJING TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311760804.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-20
Publication Date
2025-04-18
Estimated Expiration
2043-12-20

AI Technical Summary

Technical Problem

In the process of using ceramic granules as aggregate to make building materials, there is a contradiction between the low density and high strength of ceramic granules. The prior art is difficult to meet the two performance requirements of low bulk density and high cylinder pressure strength of ceramic granules at the same time.

Method used

Cast ash is used as raw material, and the use of AC foaming agent and oxidizing agent is combined with the use of a low-temperature firing technology to increase the porosity and strength of the ceramic particles. The specific steps include stirring and mixing the raw materials, forming and compacting the roller granulator and round pot granulator, followed by heating and low-temperature firing of the rotary kiln.

Benefits of technology

The low density and high strength of the ceramic particles are achieved, with a bulk density of ≤300kg/m3, a cylinder pressure strength of ≥4.2MPa, a boiling mass loss of ≤0.15%, and a burning reduction of ≤0.25%, meeting the multiple requirements for the performance of ceratops in building materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of ceramsite production, and in particular to a high-strength and low-density ceramsite fired at low temperature using foundry ash and a preparation method thereof. In terms of weight, the raw materials for its preparation include: 75 to 85 parts of component A and 15 to 25 parts of component B; wherein the component A is composed of the following raw materials in weight percentage: 93 to 98% foundry ash, 1.5 to 6% AC foaming agent, and 0.5 to 1.0% oxidant; the component B is composed of the following raw materials in weight percentage: 2 to 5% water glass, 1% strong alkali, and 94 to 97% water. The present invention reduces the density of ceramsite fired at low temperature using foundry ash as raw material by using AC foaming agent and oxidant, and uses water glass and strong alkali to stimulate the activity of the material, thereby obtaining high-strength ceramsite, so that the prepared ceramsite has a bulk density of 200 to 400 kg / m 3 The cylinder pressure strength is 3.0-4.3Mpa, which can simultaneously meet the two performance requirements of low bulk density of expanded clay and high cylinder pressure strength; it uses foundry ash as the main raw material, which is cheap and easy to obtain, is beneficial to environmental protection, and has good social and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramsite production, and in particular to high-strength and low-density ceramsite fired at low temperature using foundry ash and a preparation method thereof. Background Art

[0002] High-strength ceramsite refers to light coarse aggregate for structure with strength not less than 25MPa and cylinder compressive strength above 4.0MPa. Thanks to the characteristics and advantages of this material, such as light weight, high strength, thermal insulation, etc., it has been widely used in high-rise buildings, bridges and large-span concrete structure projects.

[0003] However, in the process of using ceramsite as aggregate to make building materials, there is a contradiction between the low density and high strength of ceramsite. In order to reduce the density of ceramsite, air-entraining components are usually added to the raw material, and the roasting temperature is increased to increase the gas content inside the ceramsite, so that its porosity increases and the density decreases. However, since ceramsite produces a large amount of gas during the roasting process and the roasting temperature is high, these gases will form interconnected pores inside the ceramsite, resulting in a significant decrease in its mechanical properties. In order to improve the strength of ceramsite, it is usually necessary to increase the glass phase content and density after the raw material is melted, which requires reducing the content of air-entraining components and the roasting temperature. In this way, the mechanical properties of the obtained ceramsite can be improved, but its density will increase accordingly.

[0004] Foundry dust is a powdery waste from foundries. It is mainly derived from the powdered solid waste generated by the sand processing department during the production of castings and collected by dust removal equipment. It has a high loss on ignition and contains rich SiO2 and Al2O3. At present, these foundry dusts are mainly used in low value-added fields such as construction projects, mine backfilling, and road projects. However, the rich substances contained in them have not been effectively utilized. Therefore, it is of great significance to prepare ceramsite from foundry dust. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a high-strength and low-density ceramsite fired at low temperature using foundry ash and a preparation method thereof. The ceramsite of the present invention can simultaneously meet the two performance requirements of low ceramsite bulk density and high cylinder pressure strength.

[0006] To achieve the above objectives, the present invention adopts the following technical solutions.

[0007] On the one hand, the present invention provides a high-strength and low-density ceramsite fired at low temperature using foundry ash. The raw materials for its preparation include, by weight: 75-85 parts of component A and 15-25 parts of component B; wherein the component A is composed of the following raw materials in weight percentage: 93-98% of foundry ash, 1.5-6% of AC foaming agent, and 0.5-1.0% of oxidant; and the component B is composed of the following raw materials in weight percentage: 2-5% of water glass, 1% of strong alkali, and 94-97% of water.

[0008] Furthermore, the water glass modulus is 2.5-3.0.

[0009] Furthermore, the oxidant includes at least one of potassium nitrate and potassium permanganate.

[0010] Furthermore, the strong base is a soluble inorganic strong base. Preferably, the strong base includes but is not limited to at least one of NaOH, KOH, Ca(OH)2, and Ba(OH)2.

[0011] Furthermore, the high-strength and low-density ceramsite is spherical particles with a particle size of 3 to 8 mm.

[0012] On the other hand, the present invention also provides a method for preparing high-strength and low-density ceramsite by low-temperature firing of casting ash, comprising the following steps:

[0013] (1) Stir and mix the casting ash, AC foaming agent and oxidant to form component A;

[0014] (2) dissolving water glass and a strong base in water and mixing them evenly to prepare component B;

[0015] (3) mixing the component A and the component B uniformly, pressing and molding the components using a double-roll granulator, and compacting the molded particles using a round pot granulator to obtain ceramsite green embryos;

[0016] (4) placing the ceramsite embryos in a room and leaving them to stand for 24 hours before heating them;

[0017] (5) After being placed in a rotary kiln for low-temperature firing, it is slowly cooled to room temperature to obtain a finished product.

[0018] Furthermore, the stirring and mixing in step (1) is carried out using a high-speed stirrer with a barrel speed of 200-300 r / min and a rotor speed of 3000-4000 r / min.

[0019] Furthermore, in step (3), the pressing process is performed to produce particles of 3-8 mm, and the compaction time is 30 minutes.

[0020] Furthermore, the temperature raising treatment in step (4) is to use hot air to heat to 190-200° C. and keep the temperature for 60 min-90 min.

[0021] Furthermore, in step (5), the firing temperature is 780-850° C. and the firing time is 45-80 min.

[0022] The method comprises the following steps: uniformly mixing water glass, AC special foaming agent, strong alkali, foundry ash and oxidant in a certain proportion, placing the mixture in a double-roll granulator for compression molding, and then using a round pot granulator to compact the molded particles to obtain a ceramsite embryo. The molded particles are continuously squeezed and rolled in the round pot to improve the strength of the ceramsite. The ceramsite embryo is then placed indoors for static storage, so that each component of the ceramsite has sufficient reaction time to react. The ceramsite is then subjected to a temperature increase treatment to better foam, thereby increasing the porosity of the ceramsite and reducing the density. The mixture is then placed in a rotary kiln for firing. The foundry ash has a high ignition loss, and the AC foaming agent is used to increase its volume. The oxidant is used to provide an oxidizing environment during the firing process to fully burn the combustibles in the foundry ash, thereby obtaining low-density ceramsite. The activity of the material is stimulated by using water glass and strong alkali to obtain high-strength ceramsite.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention utilizes a method for low-temperature firing of foundry ash to prepare high-strength and low-density ceramsite. The foundry ash has a high ignition loss. The volume of the foundry ash is increased by using an AC foaming agent, and an oxidant is used to provide an oxidizing environment during the firing process to fully burn the combustibles in the foundry ash, thereby obtaining low-density ceramsite. The granules pressed and formed by a double-roll granulator are compacted by using a round pot granulator, and the activity of the material is stimulated by using water glass and a strong alkali, thereby obtaining high-strength ceramsite. Therefore, the ceramsite of the present invention can simultaneously meet the two performance requirements of low bulk density and high cylinder pressure strength.

[0025] 2. The main raw material of the high-strength and low-density ceramsite of the present invention is foundry dust, and the required raw materials are cheap and easily available. The solid waste of the foundry industry is recycled, which is beneficial to environmental protection and has good social and economic benefits. DETAILED DESCRIPTION

[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0027] Example 1

[0028] The present embodiment provides a high-strength and low-density ceramsite fired at low temperature using foundry ash. The raw materials for its preparation include, by weight: 75 parts of component A and 25 parts of component B; wherein component A is composed of the following raw materials in weight percentage: 93% foundry ash, 6% AC foaming agent, and 1% potassium nitrate; component B is composed of the following raw materials in weight percentage: 2% water glass, 1% sodium hydroxide, and 97% water;

[0029] The preparation process is as follows:

[0030] (1) Component A is prepared by mixing casting ash, AC foaming agent and potassium nitrate in a high-speed mixer; the drum speed of the high-speed mixer is 200 r / min and the rotor speed is 3000 r / min;

[0031] (2) dissolving water glass and NaOH in water and mixing them evenly to obtain component B;

[0032] (3) Component A and component B are mixed evenly, pressed into 3-8 mm granules using a double-roll granulator, and then compacted into granules using a round pot granulator for 30 min to obtain ceramsite green embryos;

[0033] (4) Place the ceramsite embryo in a room and let it stand for 24 hours to allow the components of the ceramsite to have enough time to react;

[0034] (5) Use hot air to heat to 190°C and keep it warm for 60 minutes to increase the porosity and reduce the density;

[0035] (6) Firing in a rotary kiln at 780°C for 45 minutes to remove organic matter and combustible substances in the casting ash and reduce the density. After firing, slowly cooling to room temperature to obtain the finished product.

[0036] The bulk density, cylinder pressure strength, boiling mass loss and ignition loss of the ceramsite prepared in this example were measured according to the national standard GB / T17431.2-2010 "Light aggregate and its test method Part 2: Light aggregate test method".

[0037] The test results of the above items are shown in Table 1.

[0038] Example 2

[0039] This embodiment provides a high-strength, low-density ceramsite fired at low temperature using foundry ash, which differs from Embodiment 1 in that the raw material ratio and process parameters of each process are different. In terms of weight, the raw materials for its preparation include: 85 parts of component A and 15 parts of component B; wherein component A is composed of the following raw materials in weight percentage: 98% foundry ash, 1.5% AC foaming agent, and 0.5% potassium nitrate; component B is composed of the following raw materials in weight percentage: 5% water glass, 1% sodium hydroxide, and 94% water;

[0040] The preparation process is as follows:

[0041] (1) Foundry ash, AC foaming agent and potassium nitrate are mixed uniformly in a high-speed mixer to obtain component A for standby use. The drum speed of the high-speed mixer is 300 r / min and the rotor speed is 4000 r / min;

[0042] (2) dissolving water glass and NaOH in water and mixing them evenly to obtain component B;

[0043] (3) Component A and component B are mixed evenly, pressed into 3-8 mm granules using a double-roll granulator, and then compacted into granules using a round pot granulator for 30 min to obtain ceramsite green embryos;

[0044] (4) Place the ceramsite embryo in a room and let it stand for 24 hours to allow the components of the ceramsite to have enough time to react;

[0045] (5) Use hot air to heat to 200 °C and keep it warm for 90 min to increase its porosity and reduce its density;

[0046] (6) Firing in a rotary kiln at 850°C for 80 minutes to remove organic matter and combustible substances in the casting ash and reduce density. After firing, slowly cooling to room temperature to obtain a finished product.

[0047] The bulk density, cylinder pressure strength, boiling mass loss and ignition loss of the ceramsite prepared in this example were measured according to the national standard GB / T17431.2-2010 "Light aggregate and its test method Part 2: Light aggregate test method".

[0048] The test results of the above items are shown in Table 1.

[0049] Example 3

[0050] This embodiment provides a high-strength, low-density ceramsite fired at low temperature using foundry ash, which differs from Embodiment 1 in that the raw material ratio and process parameters of each process are different. In terms of weight, the raw materials for its preparation include: 80 parts of component A and 20 parts of component B; wherein component A is composed of the following raw materials in weight percentage: 95% foundry ash, 4.25% AC foaming agent, and 0.75% potassium nitrate; component B is composed of the following raw materials in weight percentage: 3.5% water glass, 1% sodium hydroxide, and 95.5% water;

[0051] The preparation process is as follows:

[0052] (1) Foundry ash, AC foaming agent and potassium nitrate are mixed uniformly in a high-speed mixer to obtain component A for standby use. The cylinder speed of the high-speed mixer is 250 r / min and the rotor speed is 3500 r / min;

[0053] (2) dissolving water glass and NaOH in water and mixing them evenly to obtain component B;

[0054] (3) Component A and component B are mixed evenly, pressed into 3-8 mm granules using a double-roll granulator, and then compacted into granules using a round pot granulator for 30 min to obtain ceramsite green embryos;

[0055] (4) Place the ceramsite embryo in a room and let it stand for 24 hours to allow the components of the ceramsite to have enough time to react;

[0056] (5) Use hot air to heat to 195°C and keep it warm for 75 minutes to increase the porosity and reduce the density;

[0057] (6) Firing in a rotary kiln at 820°C for 60 minutes to remove organic matter and combustible substances in the casting ash and reduce density. After firing, slowly cooling to room temperature to obtain a finished product.

[0058] The bulk density, cylinder pressure strength, boiling mass loss and ignition loss of the ceramsite prepared in this example were measured according to the national standard GB / T17431.2-2010 "Light aggregate and its test method Part 2: Light aggregate test method".

[0059] The test results of the above items are shown in Table 1.

[0060] Example 4

[0061] This embodiment provides a high-strength, low-density ceramsite fired at low temperature using foundry ash. The difference between this embodiment and embodiment 1 is that potassium permanganate is used as an oxidant instead of potassium nitrate, and potassium hydroxide is used as a strong base instead of sodium hydroxide. In terms of weight, the raw materials for its preparation include: 75 parts of component A and 25 parts of component B; wherein component A is composed of the following raw materials in weight percentage: 93% foundry ash, 6% AC foaming agent, and 1% potassium permanganate; component B is composed of the following raw materials in weight percentage: 2% water glass, 1% potassium hydroxide, and 97% water;

[0062] The preparation process is as follows:

[0063] (1) Component A is prepared by mixing casting ash, AC foaming agent and potassium permanganate in a high-speed mixer; the drum speed of the high-speed mixer is 200 r / min and the rotor speed is 3000 r / min;

[0064] (2) dissolving water glass and KOH in water and mixing them evenly to obtain component B;

[0065] (3) Component A and component B are mixed evenly, pressed into 3-8 mm granules using a double-roll granulator, and then compacted into granules using a round pot granulator for 30 min to obtain ceramsite green embryos;

[0066] (4) Place the ceramsite embryo in a room and let it stand for 24 hours to allow the components of the ceramsite to have enough time to react;

[0067] (5) Use hot air to heat to 190°C and keep it warm for 60 minutes to increase the porosity and reduce the density;

[0068] (6) Firing in a rotary kiln at 780°C for 45 minutes to remove organic matter and combustible substances in the casting ash and reduce the density. After firing, slowly cooling to room temperature to obtain the finished product.

[0069] Example 5

[0070] This embodiment provides a high-strength, low-density ceramsite fired at low temperature using foundry ash. The difference between this embodiment and embodiment 1 is that potassium permanganate is used as an oxidant instead of potassium nitrate, and calcium hydroxide is used as a strong base instead of sodium hydroxide. In terms of weight, the raw materials for its preparation include: 75 parts of component A and 25 parts of component B; wherein component A is composed of the following raw materials in weight percentage: 93% foundry ash, 6% AC foaming agent, and 1% potassium permanganate; component B is composed of the following raw materials in weight percentage: 2% water glass, 1% Ca(OH)2, and 97% water;

[0071] The preparation process is as follows:

[0072] (1) Component A is prepared by mixing casting ash, AC foaming agent and potassium permanganate in a high-speed mixer; the drum speed of the high-speed mixer is 200 r / min and the rotor speed is 3000 r / min;

[0073] (2) dissolving water glass and Ca(OH)2 in water and mixing them evenly to obtain component B;

[0074] (3) Component A and component B are mixed evenly, pressed into 3-8 mm granules using a double-roll granulator, and then compacted into granules using a round pot granulator for 30 min to obtain ceramsite green embryos;

[0075] (4) Place the ceramsite embryo in a room and let it stand for 24 hours to allow the components of the ceramsite to have enough time to react;

[0076] (5) Use hot air to heat to 190°C and keep it warm for 60 minutes to increase the porosity and reduce the density;

[0077] (6) Firing in a rotary kiln at 780°C for 45 minutes to remove organic matter and combustible substances in the casting ash and reduce the density. After firing, slowly cooling to room temperature to obtain the finished product.

[0078] Example 6

[0079] This embodiment provides a high-strength, low-density ceramsite fired at low temperature using foundry ash. The difference between this embodiment and embodiment 1 is that potassium chlorate is used as an oxidant in the raw materials instead of potassium nitrate. In terms of weight, the raw materials for its preparation include: 75 parts of component A and 25 parts of component B; wherein component A is composed of the following raw materials in weight percentage: 93% foundry ash, 6% AC foaming agent, and 1% potassium chlorate; component B is composed of the following raw materials in weight percentage: 2% water glass, 1% aluminum hydroxide, and 97% water;

[0080] The preparation process is as follows:

[0081] (1) Foundry ash, AC foaming agent and potassium chlorate are mixed uniformly in a high-speed mixer to obtain component A for standby use; the cylinder speed of the high-speed mixer is 200 r / min and the rotor speed is 3000 r / min;

[0082] (2) dissolving water glass and Al(OH)3 in water and mixing them evenly to obtain component B;

[0083] (3) Component A and component B are mixed evenly, pressed into 3-8 mm granules using a double-roll granulator, and then compacted into granules using a round pot granulator for 30 min to obtain ceramsite green embryos;

[0084] (4) Place the ceramsite embryo in a room and let it stand for 24 hours to allow the components of the ceramsite to have enough time to react;

[0085] (5) Use hot air to heat to 190°C and keep it warm for 60 minutes to increase the porosity and reduce the density;

[0086] (6) Firing in a rotary kiln at 780°C for 45 minutes to remove organic matter and combustible substances in the casting ash and reduce the density. After firing, slowly cooling to room temperature to obtain the finished product.

[0087] The bulk density, cylinder pressure strength, boiling mass loss and ignition loss of the ceramsite prepared in this example were measured according to the national standard GB / T17431.2-2010 "Light aggregate and its test method Part 2: Light aggregate test method".

[0088] The test results of the above items are shown in Table 1.

[0089] Comparative Example 1

[0090] This comparative example provides a high-strength, low-density ceramsite fired at low temperature using foundry ash. The difference between this comparative example and Example 1 is that no oxidant is used in the raw materials of this comparative example. The raw materials for its preparation include, by weight: 75 parts of component A and 25 parts of component B; wherein component A is composed of the following raw materials in weight percentage: 93% foundry ash and 6% AC foaming agent; component B is composed of the following raw materials in weight percentage: 2% water glass, 1% sodium hydroxide, and 97% water;

[0091] The preparation process is as follows:

[0092] (1) The foundry ash and AC foaming agent are mixed uniformly in a high-speed mixer to obtain component A for standby use; the cylinder speed of the high-speed mixer is 200 r / min, and the rotor speed is 3000 r / min;

[0093] (2) dissolving water glass and NaOH in water and mixing them evenly to obtain component B;

[0094] (3) Component A and component B are mixed evenly, pressed into 3-8 mm granules using a double-roll granulator, and then compacted into granules using a round pot granulator for 30 min to obtain ceramsite green embryos;

[0095] (4) Place the ceramsite embryo in a room and let it stand for 24 hours to allow the components of the ceramsite to have enough time to react;

[0096] (5) Use hot air to heat to 190°C and keep it warm for 60 minutes to increase the porosity and reduce the density;

[0097] (6) Firing in a rotary kiln at 780°C for 45 minutes to remove organic matter and combustible substances in the casting ash and reduce the density. After firing, slowly cool to room temperature to obtain the finished product.

[0098] The bulk density, cylinder pressure strength, boiling mass loss and ignition loss of the ceramsite prepared in this comparative example were measured according to the national standard GB / T17431.2-2010 "Light aggregate and its test method Part 2: Light aggregate test method".

[0099] Comparative Example 2

[0100] This comparative example provides a high-strength, low-density ceramsite fired at low temperature using foundry ash. The difference between this comparative example and Example 1 is that no alkali is used in the raw materials of this comparative example. The raw materials for its preparation include, by weight, 75 parts of component A and 25 parts of component B; wherein component A is composed of the following raw materials in weight percentage: 93% foundry ash, 6% AC foaming agent, and 1% potassium nitrate; component B is composed of the following raw materials in weight percentage: 2% water glass and 97% water;

[0101] The preparation process is as follows:

[0102] (1) Component A is prepared by mixing casting ash, AC foaming agent and potassium nitrate in a high-speed mixer; the drum speed of the high-speed mixer is 200 r / min and the rotor speed is 3000 r / min;

[0103] (2) dissolving water glass in water and mixing evenly to obtain component B;

[0104] (3) Component A and component B are mixed evenly, pressed into 3-8 mm granules using a double-roll granulator, and then compacted into granules using a round pot granulator for 30 min to obtain ceramsite green embryos;

[0105] (4) Place the ceramsite embryo in a room and let it stand for 24 hours to allow the components of the ceramsite to have enough time to react;

[0106] (5) Use hot air to heat to 190°C and keep it warm for 60 minutes to increase the porosity and reduce the density;

[0107] (6) Firing in a rotary kiln at 780°C for 45 minutes to remove organic matter and combustible substances in the casting ash and reduce the density. After firing, slowly cooling to room temperature to obtain the finished product.

[0108] The bulk density, cylinder pressure strength, boiling mass loss and ignition loss of the ceramsite prepared in this comparative example were measured according to the national standard GB / T17431.2-2010 "Light aggregate and its test method Part 2: Light aggregate test method".

[0109] The test results of the above items are shown in Table 1.

[0110] Comparative Example 3

[0111] This comparative example provides a high-strength, low-density ceramsite fired at low temperature using foundry ash. The difference between this comparative example and Example 1 is that the alkali used in the raw materials of this comparative example is weak alkali aluminum hydroxide. In terms of weight, the raw materials for its preparation include: 75 parts of component A and 25 parts of component B; wherein component A is composed of the following raw materials in weight percentage: 93% foundry ash, 6% AC foaming agent, and 1% potassium nitrate; component B is composed of the following raw materials in weight percentage: 2% water glass, 1% aluminum hydroxide, and 97% water;

[0112] The preparation process is as follows:

[0113] (1) Component A is prepared by mixing casting ash, AC foaming agent and potassium nitrate in a high-speed mixer; the drum speed of the high-speed mixer is 200 r / min and the rotor speed is 3000 r / min;

[0114] (2) dissolving water glass and Al(OH)3 in water and mixing them evenly to obtain component B;

[0115] (3) Component A and component B are mixed evenly, pressed into 3-8 mm granules using a double-roll granulator, and then compacted into granules using a round pot granulator for 30 min to obtain ceramsite green embryos;

[0116] (4) Place the ceramsite embryo in a room and let it stand for 24 hours to allow the components of the ceramsite to have enough time to react;

[0117] (5) Use hot air to heat to 190°C and keep it warm for 60 minutes to increase the porosity and reduce the density;

[0118] (6) Firing in a rotary kiln at 780°C for 45 minutes to remove organic matter and combustible substances in the casting ash and reduce the density. After firing, slowly cooling to room temperature to obtain the finished product.

[0119] The bulk density, cylinder pressure strength, boiling mass loss and ignition loss of the ceramsite prepared in this comparative example were measured according to the national standard GB / T17431.2-2010 "Light aggregate and its test method Part 2: Light aggregate test method".

[0120] The test results of the above items are shown in Table 1.

[0121] Comparative Example 4

[0122] This comparative example provides a high-strength, low-density ceramsite fired at low temperature using foundry ash. The difference between this comparative example and Example 1 is that no AC foaming agent is used in the raw materials of this comparative example. By weight, the raw materials for its preparation include: 75 parts of component A and 25 parts of component B; wherein component A is composed of the following raw materials in percentage: 93% foundry ash and 1% potassium nitrate; component B is composed of the following raw materials in percentage: 2% water glass, 1% sodium hydroxide, and 97% water;

[0123] The preparation process is as follows:

[0124] (1) Component A is prepared by mixing casting ash, AC foaming agent and potassium nitrate in a high-speed mixer; the drum speed of the high-speed mixer is 200 r / min and the rotor speed is 3000 r / min;

[0125] (2) dissolving water glass and NaOH in water and mixing them evenly to obtain component B;

[0126] (3) Component A and component B are mixed evenly, pressed into 3-8 mm granules using a double-roll granulator, and then compacted into granules using a round pot granulator for 30 min to obtain ceramsite green embryos;

[0127] (4) Place the ceramsite embryo in a room and let it stand for 24 hours to allow the components of the ceramsite to have enough time to react;

[0128] (5) Use hot air to heat to 190°C and keep it warm for 60 minutes to increase the porosity and reduce the density;

[0129] (6) Firing in a rotary kiln at 780°C for 45 minutes to remove organic matter and combustible substances in the casting ash and reduce the density. After firing, slowly cooling to room temperature to obtain the finished product.

[0130] The bulk density, cylinder pressure strength, boiling mass loss and ignition loss of the ceramsite prepared in this comparative example were measured according to the national standard GB / T17431.2-2010 "Light aggregate and its test method Part 2: Light aggregate test method".

[0131] The test results of the above items are shown in Table 1.

[0132] Comparative Example 5

[0133] This comparative example provides a high-strength, low-density ceramsite fired at low temperature using foundry ash. The difference between this comparative example and Example 1 is that in the preparation process, a round pot granulator is not used to compact the granules pressed and formed by a roller granulator. In terms of weight, the raw materials for its preparation include: 75 parts of component A and 25 parts of component B; wherein component A is composed of the following raw materials in weight percentage: 93% foundry ash, 6% AC foaming agent, and 1% potassium nitrate; component B is composed of the following raw materials in weight percentage: 2% water glass, 1% sodium hydroxide, and 97% water;

[0134] The preparation process is as follows:

[0135] (1) Component A is prepared by mixing casting ash, AC foaming agent and potassium nitrate in a high-speed mixer; the drum speed of the high-speed mixer is 200 r / min and the rotor speed is 3000 r / min;

[0136] (2) dissolving water glass and NaOH in water and mixing them evenly to obtain component B;

[0137] (3) Component A and component B are mixed evenly, and pressed into granules of 3-8 mm using a double-roll granulator to obtain ceramsite green embryos;

[0138] (4) Place the ceramsite embryo in a room and let it stand for 24 hours to allow the components of the ceramsite to have enough time to react;

[0139] (5) Use hot air to heat to 190°C and keep it warm for 60 minutes to increase the porosity and reduce the density;

[0140] (6) Firing in a rotary kiln at 780°C for 45 minutes to remove organic matter and combustible substances in the casting ash and reduce the density. After firing, slowly cooling to room temperature to obtain the finished product.

[0141] The bulk density, cylinder pressure strength, boiling mass loss and ignition loss of the ceramsite prepared in this comparative example were measured according to the national standard GB / T17431.2-2010 "Light aggregate and its test method Part 2: Light aggregate test method".

[0142] The test results of the above items are shown in Table 1

[0143] Table 1 Test results of various ceramsite properties

[0144] serial number Boiling mass loss % <![CDATA[Bulk density kg / m 3 > Cylinder pressure strength MPa Loss on ignition % Example 1 0.06 232 5.2 0.15 Example 2 0.08 247 4.8 0.20 Example 3 0.08 252 5.1 0.21 Example 4 0.06 238 4.9 0.18 Example 5 0.09 271 4.7 0.19 Example 6 0.05 287 4.2 0.25 Comparative Example 1 0.15 328 4.8 6.8 Comparative Example 2 0.08 264 2.6 0.15 Comparative Example 3 0.09 234 3.7 0.16 Comparative Example 4 0.08 663 6.2 5.7 Comparative Example 5 0.06 198 1.8 0.12

[0145] As shown in Table 1, the present invention reduces the density of ceramsite fired at low temperature using foundry ash as raw material by using AC foaming agent and oxidant, compacts the particles pressed by roller granulator by using round pot granulator, and activates the activity of material by using water glass and strong alkali, thereby improving the strength of ceramsite, and making the bulk density of the prepared ceramsite ≤300kg / m 3 , cylinder pressure strength ≥4.2MPa, boiling mass loss ≤0.15%, ignition loss ≤0.25%, which can simultaneously meet the two performance requirements of low bulk density and high cylinder pressure strength of expanded clay.

[0146] Compared with Example 1, the raw materials of Comparative Example 1 did not use an oxidant, resulting in incomplete combustion of residual combustibles in the dust ash, large ignition loss and high density; the raw materials of Comparative Example 2 did not use alkali as a reinforcing agent, resulting in lower strength of ceramsite; the raw materials of Comparative Example 3 used weak base aluminum hydroxide as an alkali reinforcing agent, resulting in low strength of ceramsite; the raw materials of Comparative Example 4 did not use AC foaming agent, resulting in no air attack of ceramsite and insufficient internal combustion during firing; Comparative Example 5 did not use a round pot granulator to compact the formed particles after pressing and molding on a double-roll granulator, resulting in low overall strength of ceramsite; therefore, the technical solution of the present invention provides strength by using a strong alkali, combines with water glass to stimulate the activity of the material, uses an AC foaming agent to increase the porosity, and combines with an oxidant (potassium nitrate and potassium permanganate) to obtain high-strength ceramsite with high porosity and less residue after firing.

[0147] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A high-strength, low-density ceramsite fired at low temperature using foundry ash, characterized in that: The raw materials for its preparation include, by weight: 75-85 parts of component A and 15-25 parts of component B; wherein, the component A is composed of the following raw materials in weight percentage: 93-98% of casting ash, 1.5-6% of AC foaming agent, and 0.5-1.0% of oxidant; the component B is composed of the following raw materials in weight percentage: 2-5% of water glass, 1% of strong alkali, and 94-97% of water; The oxidant comprises at least one of potassium nitrate and potassium permanganate; The preparation method of the high-strength and low-density ceramsite comprises the following steps: (1) Stir and mix the casting ash, AC foaming agent and oxidant to form component A; (2) dissolving water glass and a strong base in water and mixing them evenly to prepare component B; (3) mixing the component A and the component B uniformly, pressing and molding the components using a double-roll granulator, and compacting the molded particles using a round pot granulator to obtain ceramsite green embryos; (4) placing the ceramsite embryos in a room and leaving them to stand for 24 hours before heating them; (5) After being placed in a rotary kiln for low-temperature firing, it is slowly cooled to room temperature to obtain a finished product.

2. The high-strength and low-density ceramsite fired at low temperature using casting ash according to claim 1 is characterized in that: The water glass modulus is 2.5-3.

0.

3. The high-strength and low-density ceramsite fired at low temperature using casting ash according to claim 1, characterized in that: The strong base is a soluble inorganic strong base.

4. The high-strength and low-density ceramsite fired at low temperature using casting ash according to claim 1, characterized in that: The high-strength and low-density ceramsite is spherical particles with a particle size of 3 to 8 mm.

5. The high-strength and low-density ceramsite fired at low temperature using casting ash according to claim 1, characterized in that: In the step (1) of the method for preparing high-strength and low-density ceramsite, the stirring and mixing method is to use a high-speed stirrer with a barrel speed of 200-300 r / min and a rotor speed of 3000-4000 r / min.

6. The high-strength and low-density ceramsite fired at low temperature using casting ash according to claim 1, characterized in that: In step (3) of the method for preparing high-strength and low-density ceramsite, the particles are pressed and formed into particles of 3-8 mm, and the compaction time is 30 minutes.

7. The high-strength and low-density ceramsite fired at low temperature using casting ash according to claim 1, characterized in that: In the step (4) of the method for preparing high-strength and low-density ceramsite, the temperature is raised to 190-200° C. using hot air and kept warm for 60 min-90 min.

8. The high-strength and low-density ceramsite fired at low temperature using casting ash according to claim 1, characterized in that: In step (5) of the method for preparing high-strength and low-density ceramsite, the firing temperature is 780-850° C. and the firing time is 45-80 min.

Citation Information

Patent Citations

  • Lightweight ceramsite prepared from waste foundry sand and waste ash and preparation method of lightweight ceramsite

    CN107324830A

  • Preparation method of light composite ceramsite proppant

    CN107828406A

  • Refractory foundry sand and preparation method thereof

    CN109053204A

  • Recycling method of casting fly ash and sludge

    CN112573900A

  • Preparation method and application of porous geopolymer material

    CN113831068A